2021
DOI: 10.1038/s41467-020-20601-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of spin in the degradation of organic photovoltaics

Abstract: Stability is now a critical factor in the commercialization of organic photovoltaic (OPV) devices. Both extrinsic stability to oxygen and water and intrinsic stability to light and heat in inert conditions must be achieved. Triplet states are known to be problematic in both cases, leading to singlet oxygen production or fullerene dimerization. The latter is thought to proceed from unquenched singlet excitons that have undergone intersystem crossing (ISC). Instead, we show that in bulk heterojunction (BHJ) sola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 86 publications
(160 reference statements)
0
26
0
Order By: Relevance
“…[ 57–60 ] Raman and mass spectroscopy have shown the formation of C 60 oligomers, upon irradiation of neat C 60 films. [ 61 ]…”
Section: Research Challengesmentioning
confidence: 99%
“…[ 57–60 ] Raman and mass spectroscopy have shown the formation of C 60 oligomers, upon irradiation of neat C 60 films. [ 61 ]…”
Section: Research Challengesmentioning
confidence: 99%
“…2,3 Despite this promising increase in performance, rooftop stability remains arguably the most pressing challenge. Device stability can be affected by many factors including material system, 4 device architecture, 5 deposition method, 6,7 morphology, 8,9 environmental conditions, 10 and additives. 11 Devices exposed to the atmosphere are vulnerable to processes involving oxygen and water.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In an inert atmosphere the main degradation pathway in fullerene-based devices is the photo-induced dimerization of fullerene molecules, leading to a severely limited short-circuit current J sc due to photobleaching. 8,15,16 In order to avoid photo-induced dimerization, considerable attention has recently been focused on non-fullerene acceptor (NFA)-based devices. Dimerization also occurs in NFAs if the energetic alignment between donor and acceptor allows for back-hole transfer, back-electron transfer, or inter-system crossing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7] It has been shown that organic semiconductor materials, both p-and n-type, have certain issues with intrinsic photostability and undergo light-induced dimerization, cross-linking, reactions with other components of the active layer or adjacent charge-transport interlayers. [8][9][10][11][12][13][14] Hence, the design of intrinsically photostable absorber materials is a crucially important task for achieving long lifetimes in organic photovoltaics.…”
Section: Introductionmentioning
confidence: 99%